Respuesta :

Answer:

x = -33.5

Step-by-step explanation:

Step 1:  Distribute

-3(x - 3) + x = 76

(-3 * x) + (-3 * -3) + x = 76

(-3x) + (9) + x = 76

Step 2:  Combine like terms

-3x + 9 + x = 76

-2x + 9 = 76

Step 3:  Subtract 9 from both sides

-2x + 9 - 9 = 76 - 9

-2x = 67

Step 4:  Divide both sides by -2

-2x / -2 = 67 / -2

x = -33.5

Answer:  x = -33.5

Answer:

x = -33.5

Step-by-step explanation:

- 3 (x - 3) + x = 76

- 3x + 9 + x = 76

- 2x + 9 = 76

- 2x = 76 - 9

- 2x = 67

- x = 67/2

- x = 33.5

x = - 33.5

ACCESS MORE